2006
DOI: 10.1128/jcm.44.5.1686-1691.2006
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Composition of Staphylococcus aureus Isolates at a Brazilian University Hospital: Identification of International Circulating Lineages

Abstract: In only a few instances has the clonal composition of Staphylococcus aureus collections that include methicillinsusceptible S. aureus (MSSA) been extensively characterized. In order to investigate the clonal composition of MSSA and methicillin-resistant S. aureus (MRSA) and examine whether the infections diagnosed at our hospital were related to internationally distributed S. aureus lineages, we collected 89 clinical S. aureus isolates from patients at a public university hospital in Rio de Janeiro, Brazil, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 28 publications
11
80
2
3
Order By: Relevance
“…Thus, we believe that our non-BEC belonging isolates are descendants of a common ancestor, the pediatric clone, first described in Portugal, Poland, Argentina, Colombia, and in New York hospitals' pediatric patients (18,19) or from the pediatric clone NY/Japan that appeared and disseminated in Tokyo and USA hospitals (19). Although in Brazil there was a predominance of BEC in hospitals in several states (3,4,14,20) we found that there was no similarity between this clone and the isolates investigated in the present study. The ST that showed a closely related pattern also had a similar PFGE profile.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…Thus, we believe that our non-BEC belonging isolates are descendants of a common ancestor, the pediatric clone, first described in Portugal, Poland, Argentina, Colombia, and in New York hospitals' pediatric patients (18,19) or from the pediatric clone NY/Japan that appeared and disseminated in Tokyo and USA hospitals (19). Although in Brazil there was a predominance of BEC in hospitals in several states (3,4,14,20) we found that there was no similarity between this clone and the isolates investigated in the present study. The ST that showed a closely related pattern also had a similar PFGE profile.…”
Section: Resultscontrasting
confidence: 54%
“…The dissemination of the MRSA clone probably reflects their ability to cause infection and to persist and spread from one region to another, including different continents (5). The predominance of BEC (SCCmec III) in Brazilian hospitals has been well documented (3,4,14). Recent changes in the profile of clonal MRSA isolated in hospitals have been observed, which have increased the number of MRSA isolates belonging to SCCmec type IV (pediatric clone), as shown in the study by Trindade et al (15), who reported a 13% rate of occurrence of MRSA isolates in patients carrying this SCCmec admitted to a São Paulo hospital.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…[24][25][26][27] Another common MLST CC worldwide is MLST CC45, which was also highly prevalent in the present study. [25][26][27] As the Ridom SpaServer does not detect repeats longer than 24 bases, two isolates with a repeat of 25 base pairs were not type-able, in accordance with European rules for typing justified by SeqNet.org.…”
Section: Comparison With Existing Literaturementioning
confidence: 57%
“…Its resistance has been related to the predominance of epidemic PFGE (pulsed field gel eletrophoresis) clones able to expand largely around the world (Feng et al, 2008). Specifically in Brazil, a single PFGE clone A MRSA has been markedly detected as prevalent in several hospitals (Vivoni et al, 2006). The control of MRSA nosocomial infections is, many times, very difficult because of the presence of this prevalent clone.…”
Section: Introductionmentioning
confidence: 99%